Live bird market in Bangladesh: Regulatory systems and operations - Irin, Nusrat; Dilshad, Syeda Munira; Sattar, Abdullah Al; Chisty, Nurun Nahar; Sultana, Afsana; Hasan, Mahmudul; Mahmud, Rashed; Abbas, Syed Shahid; Fournie, Guillaume; Hoque, Md Ahasanul (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: In developing countries, such as Bangladesh, the live bird market (LBM) is a vital location for the trading of live poultry. The study was carried out in nine LBMs located around Bangladesh to ascertain the present regulations and procedures governing their operation. Additionally, the responsibilities and levels of engagement of the stakeholders were determined. Materials and Methods: The data were gathered through the use of a semi-structured interview guide. Thematic analysis was used to code the interview transcripts iteratively. Results: The findings indicated that the government was directly and indirectly involved in the leasing process of the markets. A market in this country is divided into numerous sectors, including LBM, fish market, vegetable market, and grocery stores. A market’s hygienic condition is highly dependent on market authority’s decisions. In some markets, market officials conducted routine sanitary inspections. Veterinarians played a little role in the inspection procedure. Conclusion: There is no adequate, functional monitoring system to ensure that LBMs adhere to cleanliness and adequate and functional biosecurity. Biosecurity enhancements, effective cleaning programs, and regular monitoring by relevant authorities are critical for LBMs in Bangladesh. J. Adv. Vet. Anim. Res., 8(4): 671–678, December 2021 http://doi.org/10.5455/javar.2021.h559